Cyanoacrylate glue for securing peripherally inserted intravenous catheters in the emergency department: A meta-analysis of randomized controlled trials. - Sciorilli, João Vitor; Remaili, João Pedro Bogossian; Silva, Davi Barbosa Pereira da; Schevz, Rodrigo Dos Reis; Machado, Amanda [UNESP]; Dalfior, Luiz (SAGE Publications, 2025)
BACKGROUND: Intravenous catheters (IVCs) are a common medical device, used in 70% of hospital patients. Due to their high failure ratio (35%-50%) and complications, we aimed to perform a systematic review and meta-analysis to assess the efficacy of Cyanoacrylate Glue (CG) use in preventing IV complications at the Emergency Department. METHODS: This study was registered in PROSPERO on February 5, 2025, with registry number CRD42025642588 and received no financial support. A systematic search at PubMed, Embase, and Cochrane databases was performed and only Randomized Controlled Trials about CG use for securing IVCs were included. RESULTS: Primary outcomes showed no statistical significance between the groups across all four outcomes at maximum follow-up. However, in a subgroup analysis including only adult patients, CG group presented lower IVCs dislodgement and failure events. Further studies in pediatric patients are needed.